Politics and Practice in Economic Geography. - Tickell, Adam (Sage Publications, 2007)
How do geographers do economic geography? This is the first sustained discussion of methodological issues in economic geography in the last twenty years. It comprises: an extended discussion of qualitative and ethnographic methods. an assessment of quantitative and numerical methods. an examination of post-structuralist and feminist methodologies. an overview of case-study approaches. an inquiry into the relation between economic geography and other disciplines. With short, accessible and engaging chapters, this is a critical assessment of qualitative and quantitative methods in economic geogr.